Epigenetic and Transcriptional Variability Shape Phenotypic Plasticity. (18th December 2017) - Ecker, Simone; Pancaldi, Vera; Valencia, Alfonso; Beck, Stephan; Paul, Dirk S.
Abstract : Epigenetic and transcriptional variability contribute to the vast diversity of cellular and organismal phenotypes and are key in human health and disease. In this review, we describe different types, sources, and determinants of epigenetic and transcriptional variability, enabling cells and organisms to adapt and evolve to a changing environment. We highlight the latest research and hypotheses on how chromatin structure and the epigenome influence gene expression variability. Further, we provide an overview of challenges in the analysis of biological variability. An improved understanding of the molecular mechanisms underlying epigenetic and transcriptional variability, at both the intra‐ and inter‐individual level, provides great opportunity for disease prevention, better therapeutic approaches, and personalized medicine. Abstract : Epigenetic and transcriptional variability mediate phenotypic plasticity, enabling adaptation to changing environments. In this review, we describe the sources of inter‐ and intra‐individual variability and discuss epigenetic regulators of gene expression variability, including DNA methylation and chromatin structure. Understanding these molecular mechanisms will improve therapeutic approaches and personalized medicine.